PENERAPAN MEDIA PEMBELAJARAN POP-UP BOOK TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK PADA MATERI PERUBAHAN BENTUK ENERGI : Artikel Penelitian - Nurul Khatimah; Irmawanty; Ana Dhiqfaini Sultan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The main issue addressed in this study is how students' learning outcomes in the IPAS subject are affected after the implementation of pop-up book learning media. This research is a type of pre-experimental study using a pre-test and post-test group design, aimed at determining students' learning outcomes following the use of pop-up book media. The population of this study consisted of all fourth-grade students at SDN No. 3 Tinambung, with a sample of 22 students. The research was conducted over five sessions, focusing on the topic of energy transformation. The data collected were analyzed using descriptive statistical techniques. The results showed that the average pre-test score was 56.73, while the average post-test score was 83.09. Furthermore, the N-Gain analysis indicated a normalized gain of 0.63, which falls into the moderate category. Therefore, it can be concluded that the use of pop-up book media led to an improvement in students' learning outcomes in the IPAS subject on the topic of energy transformation in Grade IV at SDN No. 3 Tinambung.